L’Empire en question : origines et développement d’un débat américain contemporain - Céline Letemplé (Revue LISA)
Since the end of the Cold War and even more so since the Bush administration adopted an interventionist foreign policy, the notion of Empire has reappeared in the American debate over U.S. foreign policy. If most Americans deny that the United States is an Empire, an intellectual debate opposes proponents and opponents of American imperialism. Apologists for Empire are neoconservative or liberal thinkers who share the same exceptionalist triumphalism and messianic idealism. Even though members of the Bush administration have declared that the United States is not an Empire, the 2002 National Security Strategy has neo-imperialist overtones that have triggered anti-imperialist reactions across the American political spectrum. This article gives an overview of this American intellectual debate; it shows that if the return of the imperial theme is the direct consequence of the rising influence of the neoconservatives on U.S. foreign policy, they are not the only promoters of an American Empire; and it finally argues that the mainstreaming of the formerly leftist anti-imperialist stance proceeds from the radicalization of both the discourses influencing decision-makers in Washington and the foreign adventures of the Bush administration.